Giant tumefactive perivascular spaces - Xiaodi Hao, PhD; Mingfang Zhu, MD; Leilei Tan, MD; Yue Huang, PhD; Jiewen Zhang, PhD (Radiology Case Reports, 2023)
Perivascular spaces are parts of the glymphatic pathway in the brain, which are microscopic but visible on magnetic resonance imaging when enlarged. Here, we described a case of a 16-year-old boy who presented with chronic headaches. Magnetic resonance imaging revealed giant perivascular spaces in the right centrum semiovale. Furtherly, we summarized the literature on classical and rare presentations of massive perivascular spaces and raised awareness that more clinical significance of the giant tumefactive perivascular spaces remains to be elucidated.